Clinical outcomes after initial pseudomonas acquisition in cystic fibrosis. Issue 1 (18th March 2014) - Zemanick, Edith T.; Emerson, Julia; Thompson, Valeria; McNamara, Sharon; Morgan, Wayne; Gibson, Ronald L.; Rosenfeld, Margaret; the EPIC Study Group
Summary Objectives To evaluate clinical outcomes associated with initial isolation of Pseudomonas aeruginosa (Pa) in a large U.S. cystic fibrosis (CF) cohort in the current era of widespread early Pa eradication therapy. Methods Participants were children with CF enrolled in the Early Pseudomonas Infection Control (EPIC) Observational Study who had no isolation of Pa from respiratory cultures prior to enrollment. Population‐averaged regression models using generalized estimating equation methods were used to estimate the effect of Pa acquisition on endpoints including lung function, growth, pulmonary exacerbation rate, respiratory signs and symptoms, and respiratory cultures. Results Eight hundred thirty‐eight subjects were observed for a mean 4.6 (SD 1.2) years during which 431 (51%) acquired Pa. There was no statistically significant effect of Pa acquisition on the slopes of FEV1% predicted or growth parameters. Pulmonary exacerbation rate was statistically significantly greater after Pa acquisition (incident rate ratio 1.40, 95% CI 1.07, 1.84) as were odds of crackles or wheeze on physical exam (OR 1.23, 95% CI 1.00, 1.52). Odds of isolation of MRSA (OR 1.86, 95% CI 1.38, 2.49) and S. maltophilia (OR 2.11, 95% CI 1.49, 2.98) increased after Pa acquisition, while the odds of H. influenzae (OR 0.54, 95% CI 0.46, 0.64) decreased. Conclusions In this large U.S. cohort, we did not detect an association between acquisition of Pa and deterioration in lung function or nutrition. Pa acquisition was associated with significantly increased pulmonary exacerbation rate and odds of crackles or wheeze. Pa infection may be the cause of these outcomes or a marker of more severe disease. Pediatr Pulmonol. 2015; 50:42–48. © 2014 Wiley Periodicals, Inc.